Differences in the survival of patients with recurrent versus de novo metastatic KRAS‐mutant and EGFR‐mutant lung adenocarcinomas. Issue 12 (17th March 2015) - Yu, Helena A.; Sima, Camelia S.; Hellmann, Matthew D.; Naidoo, Jarushka; Busby, Natalie; Rodriguez, Katherine; Riely, Gregory J.; Kris, Mark G.
<x xml:space="preserve">Abstract</x> BACKGROUND Prognostic variables are independently associated with survival and are fundamental to clinical trial design. In the current study, the authors evaluated the impact of stage of disease at the time of the initial diagnosis on overall survival (OS) in 2 independent, oncogene‐defined cohorts. METHODS All patients with epidermal growth factor receptor (EGFR)‐mutant and KRAS‐mutant metastatic lung adenocarcinomas were identified through routine molecular testing from January 2005 through January 2011. Clinical characteristics were obtained. OS from the date of diagnosis of recurrent or de novo metastatic disease was estimated using the Kaplan‐Meier method. RESULTS A total of 635 patients with KRAS‐mutant and 496 patients with EGFR‐mutant metastatic lung adenocarcinomas were identified. Among patients with KRAS‐mutant lung adenocarcinomas, those with de novo metastatic disease were found to have a shorter median OS compared with those with recurrent metastatic disease (13 months vs 18 months; P = .003). In a multivariable analysis of patients with KRAS‐mutant lung adenocarcinomas, de novo metastatic disease at the time of diagnosis (TNM stage IV vs stage I‐III: hazard ratio, 1.5 [95% confidence interval, 1.2‐1.8]; P<.001) was independently associated with shorter OS. In patients with EGFR‐mutant lung adenocarcinomas, after controlling for age and Karnofsky performance status, de novo metastatic disease at the time of diagnosis (stage IV vs stage I‐III: hazard ratio, 1.3 [95% confidence interval, 1.0‐1.7]; P = .03) was found to be independently associated with shorter OS. CONCLUSIONS Among patients with KRAS‐mutant lung adenocarcinomas, stage of disease at diagnosis was associated with OS from the time of diagnosis of recurrent/metastatic disease. In multivariable analyses, in both patients with EGFR‐mutant and KRAS‐mutant lung adenocarcinomas, advanced stage at the time of diagnosis was found to be independently associated with shorter survival. Stage at diagnosis is a prognostic variable that should be accounted for in prospective studies in patients with metastatic lung adenocarcinomas. Cancer 2015;121:2078–2082. © 2015 American Cancer Society.